2019
DOI: 10.3390/su11061807
|View full text |Cite
|
Sign up to set email alerts
|

The Social Costs of Marine Litter along the East China Sea: Evidence from Ten Coastal Scenic Spots of Zhejiang Province, China

Abstract: Marine litter poses numerous threats to the global environment. To estimate the social costs of marine litter in China, two stated preference methods, namely the contingent valuation model (CVM) and the choice experiment model (CEM), were used in this research. This paper conducted surveys at ten different beaches along the East China Sea in Zhejiang province in October 2017. The results indicate that approximately 74.1% of the interviewees are willing to volunteer to participate in clean-up programmes and are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The majority of studies used either a choice experiment (CE) or a contingent valuation (CV) design to elicit people's WTP for the removal of marine litter (12 and 11, respectively). Two of them use a combination of the two methods (Loomis and Santiago, 2013;Shen et al, 2019). Only one study in our sample applies the travel cost (TC) approach (Leggett et al, 2018).…”
Section: Willingness To Pay For Marine Litter Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies used either a choice experiment (CE) or a contingent valuation (CV) design to elicit people's WTP for the removal of marine litter (12 and 11, respectively). Two of them use a combination of the two methods (Loomis and Santiago, 2013;Shen et al, 2019). Only one study in our sample applies the travel cost (TC) approach (Leggett et al, 2018).…”
Section: Willingness To Pay For Marine Litter Reductionmentioning
confidence: 99%
“…Note that Talpur et al (2018) use both, additional travel costs and entry fees. The remaining studies in this set use either (entrance) fees (Beharry-Borg and Scarpa, 2010, Talpur et al, 2018, and Shen et al, 2019; additional travel costs (Loomis andSantiago, 2013, Talpur et al, 2018) or lodging prices (Schuhmann et al, 2016 is excluded from Figure 4). In contrast, the studies of the second set mostly use taxes as payment vehicle (7; for details, see Table A.2 in the Appendix).…”
Section: Willingness To Pay For Marine Litter Reductionmentioning
confidence: 99%
“…For example, Maguire et al 115 explore changes in policies affecting the use of single-use plastic. China has two papers examining the effects of plastics on people, 116,117 one on the impacts on fisheries 118 and one concerned with wildlife impacts. 119 In general, the governance papers are concerned with summarising the threat of marine plastic debris and finding solutions to the problem.…”
Section: Governancementioning
confidence: 99%
“…In addition, the literature highlights that beachgoers express willingness to pay (WTP) for improving the scenic prospects of beaches: for example, [54] found WTP for cleaning up litter and man-made waste and [55] found motivation to pay given that beachgoers express a strong aversion to beach litter. Other studies have found WTP such as an entrance fee or increased local taxes to clean up marine litter [56,57], and the rationale is that the accumulation of marine litter will have significant negative impacts on the supply of recreational services [58].…”
Section: Introductionmentioning
confidence: 99%